Is generosity time-inconsistent? Present bias across individual and social context - Felix Kölle; Lukas Wenner (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We investigate dynamically inconsistent time preferences across contexts with and without interpersonal trade-offs. In a longitudinal experiment participants make a series of intertemporal allocation decisions of real-effort tasks between themselves and another person. Our results reveal that agents are present-biased when making choices that only affect themselves but not when choosing for others. Despite this asymmetry, we find no evidence for time-inconsistent generosity, i.e., when choices involve trade-offs between own and other's consumption. Structural estimations reveal no individual-level correlation of present bias across contexts. Discounting in social situations thus seems to be conceptually different from discounting in individual situations.
Keywords: C91; D64; D90; 330; Present bias; altruism; stability; real effort; dictator game; intertemporal choice